Modeling and Kinematics Simulation of Elliptical Gears with Double Circular Arc Profiles - Yuan Xinmei; Yang Lizhao; Huang Tiancheng; Tang Wei (Jixie chuandong)
In order to meet the requirements of variable transmission ratios and improve the bearing capacity of gear teeth, a new type of double-circular-arc tooth profile elliptical gear is proposed based on the meshing theory and the structural parameter characteristics of the double-circular-arc tooth circular profile curve. The design method of its pitch curve is described. A three-dimensional model of the double-circular-arc tooth circular profile elliptical gear is established using SolidWorks software. Adams software is used to simulate the kinematics of the elliptical gear pair model with double-circular-arc tooth profiles, and the influence of different eccentricities on the variation rule of the double-circular-arc gear pair transmission ratio is analyzed; compared with the theoretical transmission ratio curve, the influencing factors of the fluctuation error of the simulation transmission ratio curve are analyzed. In order to reduce the vibration pulse of the gear pair, the appropriate value range of eccentricities is given. The design method and analysis results in this study have theoretical reference value for parametric design of non-circular gears with double-circular-arc tooth profiles, and can provide a basis for NC manufacturing and application of elliptic gear pairs with double-circular-arc tooth profiles.